Encountering from inside: The Vishwakarma techne heritage and “being” in experiencing architecture / Sanjeh Kumar Raman and Safial Aqbar Zakaria - Kumar Raman, Sanjeh; Aqbar Zakaria, Safial (Universiti Teknologi MARA, Perak, 2021)
The process of evolving from “inside”, inherent to the design culture of Vishwakarma craftsmen in Penang, provides a holistic link to its techne heritage to define the approach, process and ethics in designing culture, and sensual and sensible spaces. The exploration of “inside” allows us to understand our being in architecture which interconnects to all beings in the world.The role of body and human senses in perceiving a phenomenon, allows for a conscious experience, where we live through them by performing the conscious act through our body; which becomes an experiential, firstperson feature, in exploring “being” in architecture.